Efficacy and safety of PM-AR-T versus edwards MC3 rings in tricuspid regurgitation: A non-inferiority, randomized controlled trial - Zhenjun Xu; Jie Li; Wanzi Xu; Qiuyan Zong; Wenjie Ji; Yin Xu; Yunyan Su; Kunsheng Li; Dongjing Wang; Jun Pan (PLoS ONE, 2025)
Objectives Tricuspid valve repair, particularly with annuloplasty rings, is increasingly recognized as an effective treatment. PM-AR-T is a semi-rigid annuloplasty ring based on a nickel-titanium alloy which has made progress in animal models, however, studies on PM-AR-T’s performance in patients with tricuspid regurgitation (TR) are lacking. This study aimed to compare the efficacy and safety of the PM-AR-T with the Edwards MC3 ring for the TR treatment. Methods A non-inferiority, randomized controlled trial was conducted in 20 centers across China, enrolling patients with tricuspid valve disease requiring surgical repair. Patients were randomized to receive either PM-AR-T or Edwards MC3 ring. The primary endpoint was the success rate of valve repair at 6 months. Results A total of 164 patients underwent valve annuloplasty, 83 and 81 in the PM-AR-T and Edwards MC3 groups. Valve repair success rates were 92.8% and 93.8% in the PM-AR-T and Edwards MC3 groups, demonstrating non-inferiority with a difference of −1.1% (95% confidence interval [CI]: −9.5 to 7.4), which was less than the pre-specified non-inferiority margin of −10%. No significant intergroup differences were found in valve regurgitation, echocardiographic parameters, and New York Heart Association (NYHA) functional classification at any postoperative time point. At 12 months, the proportions of patients without regurgitation were comparable, 30.4% and 27.8% in the PM-AR-T and Edwards MC3 groups (P = 0.705). Improvement to NYHA functional class I status was detected in 46.2% and 45.6% of the two groups by 12 months (P = 0.893). Both rings exhibited comparable safety profiles, with no device-related serious adverse events, cardiovascular deaths, major bleeding events, severe structural damage, infective endocarditis, or thromboembolic events. Conclusions The PM-AR-T tricuspid valve semi-rigid ring is effective in improving TR, demonstrating non-inferiority to the Edwards MC3 ring, with a favorable safety profile. Clinical Trial Registration: This study was registered at Chinese Clinical Trial Registry (ChiCTR2100043007).